Повседневность первых месяцев (осень 1941 – весна 1942 годов) оккупации Харькова в устных свидетельствах и биографических документах (в контексте социологического изучения явления гражданского коллаборационизма) - Крыжный, С. (Социология: теория, методы, маркетинг, 2008)
The paper presents some outcomes of a sociological investigation of the surviving practices widespread among the inhabitants of Kharkov under Nazi occupation during the Second World War. The author applies an original research methodology combin ing biographical analysis with oral evidences by eye-witnesses. Based on qualitative methods, a sociological reconstruction of the everyday life of Kharkov’s inhabitants under the first period of the German occupation (autumn 1941 – spring 1942) is devised; usual practices for surviving and contributing factors are distinguished.